2011
DOI: 10.1186/1471-2164-12-399
|View full text |Cite
|
Sign up to set email alerts
|

A genomic biomarker signature can predict skin sensitizers using a cell-based in vitro alternative to animal tests

Abstract: BackgroundAllergic contact dermatitis is an inflammatory skin disease that affects a significant proportion of the population. This disease is caused by an adverse immune response towards chemical haptens, and leads to a substantial economic burden for society. Current test of sensitizing chemicals rely on animal experimentation. New legislations on the registration and use of chemicals within pharmaceutical and cosmetic industries have stimulated significant research efforts to develop alternative, human cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
116
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(126 citation statements)
references
References 51 publications
7
116
0
1
Order By: Relevance
“…Many molecular processes involving skin sensitization have been identified (Martin et al, 2011;van der Veen et al, 2011), the role of these mechanisms in driving biomarker expression is often not known. In recent gene profiling studies it was shown both in dendritic cells as well as in keratinocytes that the cytoprotective Nrf2-Keap1 and the innate immunity-related Toll-like receptor (TLR) signaling pathways are triggered upon exposure to chemical sensitizers (Ade et al, 2009;Johansson et al, 2011;van der Veen et al, 2013b). In this study, the role of these pathways in driving the biomarkers heme oxygenate1 (HMOX1) and interleukin (IL)-8 was further established.…”
Section: Introductionmentioning
confidence: 83%
“…Many molecular processes involving skin sensitization have been identified (Martin et al, 2011;van der Veen et al, 2011), the role of these mechanisms in driving biomarker expression is often not known. In recent gene profiling studies it was shown both in dendritic cells as well as in keratinocytes that the cytoprotective Nrf2-Keap1 and the innate immunity-related Toll-like receptor (TLR) signaling pathways are triggered upon exposure to chemical sensitizers (Ade et al, 2009;Johansson et al, 2011;van der Veen et al, 2013b). In this study, the role of these pathways in driving the biomarkers heme oxygenate1 (HMOX1) and interleukin (IL)-8 was further established.…”
Section: Introductionmentioning
confidence: 83%
“…The myeloid cell line used in this study was derived from MUTZ-3 (DSMZ, Braunschweig, Germany) and maintained as described (Johansson et al, 2011(Johansson et al, , 2013. A phenotypic control analysis of the cells prior to each experiment was carried out by flow cytometry in order to confirm the cells' immature state.…”
Section: Cells and Flow Cytometrymentioning
confidence: 99%
“…The resulting biomarker signature, the GARD prediction signature (GPS), consists of 200 transcripts, which are used as input into a support vector machine (SVM) model trained on a set of reference chemicals (Johansson et al, 2011). The changes in transcription can be linked to the maturation and activation of dendritic cells (KE3) during sensitization.…”
Section: Cells and Flow Cytometrymentioning
confidence: 99%
“…Extensive genomic analysis of MUTZ-3 cells has identified genes describing eight dominating functions. The primary pathways of skin sensitization induction involve signalling through transcription factors Nrf2 and aryl hydrocarbon receptor (AHR), and protein ubiquitination [37]. Monocyte-derived dendritic cells (Mo-DCs) and human monocytic leukaemia cell line (THP-1) exposed to haptens induce the Nrf2 pathway when exposed to chemicals exerting cysteine and cysteine/lysine reactivity.…”
Section: Available Animal-free Testing Approaches Cover the Moa For Smentioning
confidence: 99%
“…Functional and transcriptional analysis of various myeloid cell lines has clearly demonstrated the significance of the MUTZ-3 cell line as a model for functional studies of inflammatory responses [38]. The genomic allergen rapid detection (GARD) test is a MUTZ-3-based assay for assessing chemical sensitizers utilizing genomic biomarker prediction signatures to generate prediction calls of unknown chemicals as skin sensitizers, respiratory sensitizers or nonsensitizers, including irritants [37]. The predictive performance of the skinGARD was assessed in an in-house validation study.…”
Section: Available Animal-free Testing Approaches Cover the Moa For Smentioning
confidence: 99%